Análise setorial das características organizacionais e do nível de efetividade dos processos gerenciais de empresas de construção civil - Maia, Alessandra Tourinho (2014)
The organizational characteristics and the level of effectivity of management processes are some of the variables that determine the efficiency of running a company. If there are gaps in these aspects, the company will have difficulties in performing its activities competently. Due to the importance of organizational structure on company’s performance, this research aims to present an analysis of the organizational characteristics and the principal management processes of construction companies, of five different sectors of activity, located in the region of Curitiba, in the state of Paraná. Therefore and applied, descriptive and quantitative research was developed. The Survey Method was chosen as the basic procedure for this study, allowing the obtaining of primary data systematically. The data were analyzed using descriptive and inferential statistics, with the application of multivariate techniques of factorial analysis, discriminant analysis and cluster analysis. In general, it is observed that these companies are characterized by the delayed traditionalism of the sector, which predominates the existence of hierarchical structures with a high level of centralization, low investment in the training of staff and little concern for environmental impacts. On the other hand, due to the market dynamism, companies seek to invest in new technologies and different forms of management as a way to overcome its shortcomings, seek competitiveness and customer preference. The research results indicate that there is no significant differences in the organizational characteristics and in the level of development processes among the evaluated sectors.